RANCANGAN SWEEPER FREKUENSI YANG DAPAT BERDAYA GUNA UNTUK MENDETEKSI GANGGUAN INTERFERENSI RADIO PADA SISTEM KOMUNIKASI SATELIT DI STASIUN PENGENDALI UTAMA (SPU) CIBINONG - Esthi Handarbeni; Feti Fatonah; Dian Anggraini Purwaningtyas (Politeknik Penerbangan Indonesia Curug, 2017)
The process of data transmission in the past was still using terrestrial telecommunication system, but because terrestrial telecommunication system has limited area coverage, installation time and so forth, then developed telecommunication system by using satellite. Along with the development of technology, communication needs by using satellites is also increasing. Changes in the global environment and rapidly growing telecommunication technologies have led to a change in the way of view in telecommunication provision, so the need for structuring of national telecommunications. In 1980 Indonesia established a business entity for international telecommunication service called PT. Indonesian Satellite Coorporation (INDOSAT) which is separate from PERUMTEL. Based on PP No.25 / 1991 PERUMTEL changed into a company company (Persero) Telekomunikasi Indonesia. Telecommunication operation specifically for meteorological and geophysical purposes, broadcast radio and television, navigation, aviation, search and rescue, and so forth. In the course of its operation, satellite communications systems are not spared from a variety of disorders. One of the problems that often arise in the implementation of satellite communications is radio interference. Radio interference is a disorder generated by radio frequency induced radio stations (88-108 MHz) and is transmitted to satellites. One of the new cases occurred in February 2015, where one of the radio broadcasts detected by the Satellite Communications Control Unit (Dalkomsat) was transmitted to the Telkom-1 satellite. This interference may cause the carrier signal transmitted by satellite subscriber station Telkom-1 to be degraded. In addition, the impact of this interference also affects the satellites themselves, such as the burden on the transponder increases so that the transponder becomes over-saturated, and the most fatal of causing damage to the satellite.